Perancangan permainan dakon menggunakan C++ dan GLUT - Temia Wahyuningrum (JUITA : Jurnal Informatika, 2013)
Dakon is one of Indonesian traditional game which is now rarely played by children. After long time, this game will be extinct. Whereas traditional game has several advantages including speed and accuracy. Hence came the idea to develop dakon game into a more modern form of the media through the computer. Game designed and built using the language C++ and GLUT as computer graphics. From the results of testing by a team of product developers, game dakon been going well, and have met the criteria of verification testing, validation and exploration